Chronic vasculitis and polyneuropathy due to infection with Bartonella henselae - Schoerner, Christoph; Harrer, Thomas; et al. (Infection, 2007)
Bartonella henselae, the causative agent of cat scratch disease and bacillary angiomatosis, is associated with an expanding spectrum of diseases. Here, we report on a 40-year-old patient suffering from chronic recurrent painful ulcers of the toes, distal axonal sensomotor polyneuropathy and Raynaud's phenomenon. Biopsy of the sural nerve demonstrated an axonal neuropathy with a neurogenic muscular atrophy. Treatment with high dose corticosteroids had no beneficial effect. A biopsy taken from a recurring ulcer 7 years after the beginning of the disease revealed superficial ulcerated hyperkeratosis with subepithelial proliferation of small vessels compatible with a diagnosis of verruca peruana, however, without detection of microorganism. Serologic analysis revealed an elevated IFT titer of 1:1,024 against B. henselae. Treatment with erythromycin induced healing of the ulcer, remission of the vasculitis and the polyneuropathy, and a decline of the IFT titer. This case illustrates that B. henselae infection should be considered in patients with vasculitis and polyneuropathic syndromes. © 2007 Urban & Vogel.
UnivIS-Import:2015-04-14:Pub.2007.med.IKMI.LHMMIPDR.chroni